Effect of Core Stability Exercise in Preventing Diastasis Recti Abdominis among Normal Birth Delivery of Postpartum Mothers: Meta-Analysis - Oktaviyani, Feny; Pamungkasari, Eti Poncorini; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Diastasis Recti Abdominis (DRA) is a separation that occurs in the abdominal muscles, namely between the two rectus abdominis muscles. This separation is precisely in the linea alba which is the midline of the abdomen. DRA is characterized by two things, namely the widening of the inter-recti distance (IRD) and the appearance of a bulge in the abdomen. This is due to stretching and weakness of the linea alba. This study aims to analyze the effect of core stability exercise on reducing diastasis recti abdominis in normal postpartum mothers based on the results of a number of previous primary studies.Subjects and Method: This study uses a meta-analysis method with articles searched using the search keywords